The Role of Dance Education for Personality Development of Upper Primary School Students - Singh, Huidrom Rakesh; Devi, Laimayum Subhadra (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2021)
This paper studies the history of dance education in Manipur and social value, psychomotor domain, and creative development of students at the school curriculum in Manipur (India). Dance education plays an essential role in molding a person into a perfect human being with good health and behaviour in society. It also furnishes the essential elements humans need to live in our society other than imparting knowledge and skills. In overall development, Manipuri dance plays the most crucial role in the school curriculum. The descriptive research method used in this study revealed the importance and the role of dance education for the four upper primary school students, i.e., class VI to class VIII of Imphal West District and Imphal East District, where dance class had been adopted as one of the subjects in these schools. The 915 students have been taken from the following four schools: Kendriya Vidyalaya-Lamphelpat, Tolchou Ibeton Memorial Academy-Hiyangthang, Rajkumari Sanatombi Devi Vidyalaya-Haotal Pangei, and SL Arena of Learning-Khurai Khaidem Leikai. The researcher collected 70% of students’ respondents, of which 287 are males and 343 are females out of 630 students. Finally, the investigator has found that the social value of students is significantly improving due to dance education. Dance education helped in realizing one’s own potential for self-enhancement, confidence, problem-solving, and creativity among the students. Moreover, it also developed and enhanced the psychomotor domain and the students’ creativity to a certain extent. Thus, dance education should be made compulsory as a curriculum subject at all levels of schools.